New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina - Ailán-Choke, Lorena Gisela; Ramallo, Geraldine; Davies, Dora (Zootaxa, 2017)
During a parasitological survey, we reported specimens of a new species of Raphidascaris (Sprentascaris) in Rineloricaria steinbachi from La Caldera River, province of Salta, Northwest Argentina. The new species, R. (S.) saltaensis sp. nov., is characterized by possessing 16 pairs of preanal papillae, lips with lateral protrusions and membranous elevations, and mature eggs rough-shelled with striations. This is the sixth species of the genus described in the Neotropical Region, and the second from Argentina. Rineloricaria steinbachi is reported as host of this nematode genus for the first time. A key to the species of Raphidascaris (Sprentascaris) in the Neotropical realm is provided. Also, zoogeographical and host information of the species, belonging to the subgenus Sprentascaris, is summarized.